REFLEKSI HASIL PISA DAN TIMSS DI INDONESIA: UPAYA PENINGKATAN KOMPETENSI LITERASI SISWA MADRASAH MELALUI AKMI - Afryansyah; Aisyah; Kasinyo Harto; Amilda; Komariah Hawa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low results of international assessments PISA and TIMSS highlight major challenges in Indonesian students' literacy competencies, including in madrasah institutions. This study employed a literature review method to analyze Indonesian students' literacy achievements and government efforts to enhance literacy skills through the Indonesian Madrasah Competency Assessment (AKMI). The findings reveal that although Indonesia slightly improved its ranking in PISA 2022, it still ranks among the low-performing countries, and its absence from recent TIMSS cycles underscores the need for educational reforms. AKMI is considered a strategic initiative to enhance madrasah students' literacy, covering reading, numeracy, science, and socio-cultural literacies, aligning with the six core global literacies. However, implementation challenges such as technical readiness, infrastructure limitations, and follow-up actions on assessment results require serious attention. Collaborative efforts are needed to optimize AKMI’s role in improving the quality of madrasah education.